Mechanism of HSP90 Inhibitor in the Treatment of DSS-induced Colitis in Mice by Inhibiting MAPK Pathway and Synergistic Effect of Compound Sophorae Decoction - Yuan, Yuyi; Wu, Hui; Shuai, Bo; Liu, Chang; Zhu, Feng; Gao, Fei; Wei, Chunzhu; Fan, Heng (Current Pharmaceutical Design, 2022)
Background: The mechanism of Heat Shock Protein 90 (HSP90) in Ulcerative Colitis (UC) has been studied, and mitogenic-activated protein kinases (MAPK) also contribute to the pathogenesis of UC. However, the effect of the HSP90/MAPK pathway in UC is still unclear. Therefore, the mainstay of this research is to explore the mechanism of action of this pathway in UC. Compound sophorae decoction (CSD), as a Chinese herbal decoction, can synergistically affect the above process. Objective: This study aimed to uncover the synergistic effects of HSP90 inhibitors regulating the MAPK pathway for treating DSS-induced colitis in mice and the synergistic effects of CSD. Methods: This experiment used oral administration of standard diets containing 3% dextran sodium sulfate (DSS) to establish an experimental colitis model in mice. The model was treated with HSP90 inhibitor, CSD, or dexamethasone. Mouse feces, mobility, body weight, colon length, and colon histopathology scores were recorded daily to assess the degree of colitis inflammation. Expression levels of HSP90 and MAPK pathway-related genes and proteins were evaluated by Western blot and qPCR. The evaluation of intestinal mucosal permeability was measured by enzyme-linked immunosorbent assay (ELISA), which could detect the protein level of D-Amino Acid Oxidase (DAO) and D-lactic acid (D-LA). The same went for downstream molecules AFT-2, p53, and apoptosis-related proteins BAX, BCL-2, Caspase3, and survivin in the MAPK pathway. Immunohistochemical measured p-38, p-JNK, and p-ERK expressions. JAM-A and claudin-1 connexin were tested by immunofluorescence staining. The TUNEL method was for measuring the apoptosis rate of colonic epithelial cells. CBA kit determined the level of inflammatory factors of colons. Results: HSP90 inhibitor can improve the degree of pathological damage in the colon of mice treated with DSS, increase the mice's weight and the length of the colon, and significantly reduce the disease activity index (DAI) score. Intraperitoneal injection of HSP90 inhibitor can reduce the expression of MAPK pathway markers P38, JNK, ERK, and their phosphorylation and decrease the content of AFT-2 and p53, which is downstream of the MAPK pathway. In addition, treatment of the HSP90 inhibitor up-regulated the expression of anti-apoptotic proteins BCL-2 and survivin, as well as down-regulated apoptotic protein caspase3, BAX in the colon of mice with colitis. Lower levels of inflammatory factors such as IL-6, MCP-1, IFN-γ, TNF, IL-12p70, and increased IL-10 were observed after HSP90 inhibitor therapy. Furthermore, the combination treatment of CSD can enhance the effect of the single HSP90 inhibitor treatment and play a synergistic effect. Conclusion: These data suggest that an HSP90 inhibitor is available to treat UC by inhibiting the MAPK signaling pathway. This axis can restore the intestinal mucosa barrier's function by reducing intestinal mucosa's permeability and inhibiting apoptosis of intestinal epithelial cells. The specific mechanism is that HSP90 inhibitor can reduce the pathological damage and inflammation levels of colitis mice, and reduce the apoptosis rate of colonic epithelial cells and the mucosal permeability, thereby restoring the mucosal barrier function. During this process, CSD works synergistically to improve the therapeutic effect of the HSP90 inhibitor.
Keywords: JNK